Problematika Keterampilan Menulis dalam Pembelajaran Bahasa Arab pada Siswa - Nadia Royani Nasution; Syaipuddin Ritonga; Fadlan Masykura Setiyadi (An-Nuha, 2026)
This study aims to describe the problems in Arabic writing skills of eighth-grade students at Ma'had Al-Ba'tsah Al-Islamiyah, as well as the efforts made to overcome them. This study used a qualitative descriptive method. Data were collected through participant observation, semi-structured interviews, and document analysis. Data validity was strengthened through triangulation techniques, extended participation, and checking by participants (member check). The results of the study indicate the following. First, students face major difficulties in distinguishing letter shapes, dot placement, letter connection, and limitations in constructing sentences, choosing vocabulary, and expressing ideas. Second, these weak skills are influenced by linguistic factors, such as low vocabulary mastery and a lack of understanding of the rules of nahwu and sharaf, as well as non-linguistic factors such as low learning motivation, the use of conventional learning methods, minimal opportunities for independent practice, and lack of family support. Third, efforts to overcome these problems are carried out through the implementation of more varied learning strategies by teachers, such as free writing exercises, copying texts, and organizing creative activities. In addition, students also took the initiative to practice writing independently, keep diaries, join study groups, and take additional lessons. This study recommends implementing more diverse and contextual learning approaches, such as project-based learning, collaborative writing, language games combined with concept maps, ongoing writing practice, appreciation of student work, and the creation of a communicative classroom environment.